Does Satellite Chlorophyll‐a Respond to Southernmost Patagonian Dust? A Multi‐year, Event‐Based Approach. Issue 12 (8th December 2020) - Cosentino, N. J.; Ruiz‐Etcheverry, L. A.; Bia, G. L.; Simonella, L. E.; Coppo, R.; Torre, G.; Saraceno, M.; Tur, V. M.; Gaiero, D. M.
Abstract: Mineral aerosols may affect global climate indirectly by enhancing net primary productivity (NPP) upon deposition to the oceans and associated atmosphere‐to‐ocean CO2 flux. This mechanism is hypothesized to have contributed significantly to the last interglacial‐to‐glacial climatic transition. However, the dust‐NPP connection remains contentious for the present‐day climate system. We analyze the impact of southernmost Patagonian dust emissions on southwestern Atlantic Ocean continental shelf and proximal open ocean satellite chlorophyll‐a concentration. We use the first decadal time series of surface dust mass flux in southern Patagonia, along with in situ visibility data, to model dust emission, transport, and deposition to the ocean. We then perform a dust event‐based analysis of chlorophyll‐a time series, using a novel approach by which time series are corrected for post‐depositional particle advection due to ocean currents. Finally, we performed chemical analysis of iron in dust samples, a key micronutrient limiting phytoplankton biomass in high‐nutrient, low‐chlorophyll oceans such as offshore of the 200‐m isobath off Patagonia. We find no compelling evidence for an influence of dust as an enhancer of phytoplankton biomass either on shelf or proximal open ocean waters of the southwestern Atlantic Ocean. For open ocean waters this is consistent with a lack of source‐inherited bioavailable iron in dust samples. Future case studies addressing similar questions should concentrate on dust sources with identified high contents of bioavailable iron, particularly in the Southern Hemisphere where atmospheric processing of iron is weak. Key Points: We present the first decadal time series of surface dust mass flux in Patagonia The first event‐based study in the southwestern Atlantic Ocean shows no evidence for an influence of dust on chlorophyll‐a concentrations Source‐inherited low concentrations of bioavailable iron preclude enhancement of primary producers' biomass in proximal open ocean waters